Changes in vasoactive intestinal polypeptide (VIP) levels in the rabbit oviduct at different hormonal stages. An immunohistochemical study. - Menghi, G (1990)
In this study we investigated immunohistochemically the distribution of VIP in ampullary and isthmic segments of the rabbit oviduct at different hormonal stages in order to correlate the presence of VIP with the morphological and functional differences between the two oviduct segments. Noticeable changes in the VIP-positive sites emerged between corresponding oviduct segments during the stages examined. A reduction in VIP presence was noted in oestrus and the lowest VIP values occurred one and three days after mating in the ampulla and the isthmus respectively. In the subsequent stages an increase of VIP was noted in both tracts which showed features comparable to that described in anoestrus. The levels and distribution of VIP is correlated with the functions of the oviduct segments concerned with egg transport and formation of a mucopolysaccharide envelope around blastocysts.